Comparison of Protein Content and Physicochemical Characteristics of Fresh Noodles Enriched with Tuna and Mackerel Fish Flours - Widnyani, Ida Ayu Putu Ary; Sintyadewi, Putu Rima (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Noodle products are classified as low-nutrient noodles because they have a high carbohydrate content but low protein, vitamins and minerals. Marine fish such as tuna and mackerel are food ingredients with high protein content, and they are abundant in Indonesia. The purpose of this study was to partially substitute wheat flour with tuna flour and mackerel flour and analyze the physical (rehydration power, cooking loss, elasticity power) and chemical (protein) characteristics of the resulting wet noodles. The data obtained were analyzed statistically using a simple group randomized design and repeated 3 times. The results showed that the physical and chemical characteristics of wet noodles with the addition of mackerel flour had a cooking loss value of 11.51-16.42%, elasticity value of 29.82-17.12 gf, rehydration power of 177.33-140.65%, and protein 11.25-15.24% db. The addition of tuna fishmeal to wet noodles has a cooking loss value of 15.11-20.03%, elasticity value of 30.12-19.22 gf, rehydration power of 183.15-160.72%, and protein 13.37-21.72% db. The addition of mackerel flour and tuna flour to wet noodle products increased protein content while affecting the product's physical properties. It is hoped that this research can provide comparative insights into the utilization of marine resources as fortification ingredients in noodle products.